2009
DOI: 10.1007/s10584-009-9602-6
|View full text |Cite
|
Sign up to set email alerts
|

A forced response to twentieth century climate conditions of two Spanish forests inferred from widths and stable isotopes of tree rings

Abstract: This dendroclimatological research is based on two close pine forests (Pinus sylvestris and Pinus uncinata) located at the Northern Iberian System (Spain), and three tree-ring variables (ring widths, δ 13 C and δ 18 O). The climate-tree growth system was assessed at local and regional scales using three climate datasets. Calibration of tree-ring records with climate showed a diversity of information recorded in the different variables, such as a general response to temperature and precipitation of current grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 74 publications
2
10
1
Order By: Relevance
“…In the future, drier and warmer conditions at the onset of the growing season may cause a shift in the growth-climate association and may increase the role of the other summer months or previous conditions as observed by Andreu et al (2007) and Planells et al (2009). In these studies, the authors ascribed the upward shift in common variability observed over the twentieth century to the increasing influence of previous autumn conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, drier and warmer conditions at the onset of the growing season may cause a shift in the growth-climate association and may increase the role of the other summer months or previous conditions as observed by Andreu et al (2007) and Planells et al (2009). In these studies, the authors ascribed the upward shift in common variability observed over the twentieth century to the increasing influence of previous autumn conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them were restricted to one species or genus without clearly taking into account local conditions and highlighting temperature thresholds (Andreu et al 2007;Carrer et al 2010;Macias et al 2006;Planells et al 2009). Thus, in this study, we analysed the response patterns to climate variability over the twentieth century 95 years) of the five dominant temperate forest tree species growing under Mediterranean mountain climate (Fagus sylvatica, Abies alba, Pinus nigra, P. sylvestris and P. uncinata).…”
Section: Introductionmentioning
confidence: 99%
“…One P. nigra stand is located in the south‐east ( pn Caz), whereas the rest, two forests of P. sylvestris ( ps Lil and ps Urb) and two of P. uncinata ( pu Ped and pu Urb), are in the north. ps Urb and pu Urb are located only 10 km apart from each other, permitting the assessment of the effects of different site conditions and species‐specific responses under similar climatic conditions (Planells et al , 2009). Sampling focused on the oldest natural forest stands in the area when possible.…”
Section: Methodsmentioning
confidence: 99%
“…Although the results varied among sites and regions, most of these investigations show an enhancement in iWUE for the 20th century. In the Mediterranean area, an increasing number of studies have related δ 13 C ratios to meteorological variables (Ferrio & Voltas, 2005; Ferrio et al , 2006; Andreu et al , 2008; Correia et al , 2008; Voltas et al , 2008; Battipaglia et al , 2009; Planells et al , 2009). Others have estimated the iWUE via the extrapolations proposed above using leaves (Martínez‐Vilalta & Piñol, 2002), wood samples (Ferrio et al , 2003), 3‐year (Peñuelas et al , 2008) and 5‐year blocks from tree‐ring wood (Linares et al , 2009), as well as annual tree‐ring holocellulose over short periods (Martin‐Benito et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation